A New Distance Stereotest by Autostereoscopic Display Using an Eye-Tracking Method - Cao, Li-Qun; Wang, Yuan-Qing; Gao, Yuan; Zhou, Bi-Ye; Li, Xue-ling; Shen, Ke-Qiang; Xu, Bin; Li, Ming-Gao (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives: To present a novel Glasses-free Distance Random Dot Stereotest System (GFDRDSS) via eye tracking method. Methods: A single-view autostereoscopic display using eye tracking technique based on time-sequential principle with directional backlight structure and corresponding random dot stereotest software were developed and constituted GFDRDSS with a viewing distance of 5 meters. Stereoacuity of 12 subjects with normal eye position was evaluated by Randot Stereotests, Stereoscopic Test Charts (version 3), Distance Randot Stereotest and GFDRDSS respectively. Results: GFDRDSS could provide glasses-free stereoscopic perception which was distinct and stable even with head moving. It could evaluate disparities from 40 to 2400 arc sec. All the 11 subjects with normal near visual acuity revealed fine near stereovision (20 to 60 arc sec) by Randot and Stereoscopic Test Charts. Under refractive correction, 10 subjects presented with fine stereovision (≤60 arc sec) by GFDRDSS at distance of 5 meters, while 9 of them showed fine stereovision by Distance Randot Stereotest at 3 meters. Other subjects described the 100 arc sec-level stereogram correctly. The results exhibited a concordance of within one degrade between the two distance stereotests. Conclusion: The proposed GFDRDSS can individually project a couple of random dot stereograms to corresponding eyes of the subject, and provide glasses-free distance stereotest. It showed good concordance with the Distance Randot Stereotest. Larger data are needed for statistical studies.